Effectiveness of core biopsy for screen‐detected breast lesions under 10 mm: implications for surgical management. Issue 9 (16th March 2015) - Farshid, Gelareh; Downey, Peter; Pieterse, Steve; Gill, P. Grantley
Abstract: Background: Technical advances have improved the detection of small mammographic lesions. In the context of mammographic screening, accurate sampling of these lesions by percutaneous biopsy is crucial in limiting diagnostic surgical biopsies, many of which show benign results. Methods: Women undergoing core biopsy between January 1997 and December 2007 for <10‐mm lesions are included. Patient demographics, imaging features and final histology were tabulated. Performance indices were evaluated. Results: This audit includes 803 lesions <10 mm. Based on core histology, 345 women (43.0%) were immediately cleared of malignancy and 300 (37.4%) were referred for definitive cancer treatment. A further 157 women (19.6%) required diagnostic surgical biopsy because of indefinite or inadequate core results or radiological‐pathological discordance, and one woman (0.1%) needed further imaging in 12 months. The open biopsies were malignant in 46 (29.3%) cases. The positive predictive value of malignant core biopsy was 100%. The negative predictive value for benign core results was 97.7%, and the false‐negative rate was 2.6%. The lesion could not be visualized after core biopsy in 5.1% of women and in 4.0% of women with malignant core biopsies excision specimens did not contain residual malignancy. Excessive delays in surgery because of complications of core biopsy were not reported. Conclusion: Even at this small size range, core biopsy evaluation of screen‐detected breast lesions is highly effective and accurate. A lesion miss rate of 3.1% and under‐representation of lesions on core samples highlight the continued need for multidisciplinary collaboration and selective use of diagnostic surgical biopsy.